An Assessment of the Effect of Information and Communication Technology on Public Relations Practice in Nigeria - Nwaeke, Lawrence I.; Nsereka, Barigbon Gbara (Advances in Social Sciences Research Journal, 2016)
With the growing need to meet the demands of organizations’ publics, most of whom are technologically savvy, it has become incumbent on public relations practitioners to embrace Information and Communication Technology (ICT). It is against this background that this survey research, using the purposive sampling technique, sought to assess the effect of information and communication technology on public relations practice in Nigeria. A sample of 274 subjects was drawn from the population of the registered members of the Nigeria Institute of Public Relations (NIPR), Rivers State chapter, for the study. Findings showed, among other things, that the level of usage of ICT in PR practice in Nigeria is low; that as there are increased platforms for interaction and socialization, ICT has improved organizations’ relationship with their publics; knowledge gap on new information and communication technology tends to be the greatest challenge in the use of ICT in PR practice; and that identification of the right ICT platforms was as an effective way to utilize ICT in order to achieve set PR goals. Concluding that despite the huge potentials of ICT in reaching out to organizations’ publics, a number of public relations practitioners are still reluctant to use ICT, it was recommended, among other things, that PR practitioners be trained on ICT and other technical skills to meet the demands of the times. Training and retraining of PR practitioners was also recommended for the adoption of ICT in PR practice in Nigeria.